Pengaruh Kualitas Sumber Daya Manusia Terhadap Kinerja Pegawai - Pratidina, Ginung; Susanto, Chaerunnisa Zoe; Tri Ramdani, Faisal; Wahyudin, Cecep; Rahmawati, Rita (Universitas Djuanda Bogor, 2024)
In carrying out its duties, Bawaslu faces several problems related to employee performance, namely problems in terms of lack of employees in carrying out supervision or handling violations, discipline in using the daily uniforms of employees, coaching and improving employees, and the management system. This has an impact on the low assessment of the performance of the employees they provide. Improving optimal, effective, and efficient employee performance at work is the main goal of human resource quality. However, basically, a shortage of human resources can lead to obstacles or failures in completing tasks and achieving goals. The purpose of this study is to find out the relationship between employee performance at the Bogor Regency General Election Supervisory Agency and the quality of human resources. The method used is quantitative associative by involving all employees, namely 18 respondents as a sample. Observations, interviews, and questionnaires were used to collect data. applied the Spearman rank correlation analysis method to data analysis. The results of this research can indicate that improving the quality of human resources can maximize employee performance. The correlation coefficient obtained of 0.830 shows that a strong and positive relationship was found between employee performance and the quality of human resources. The results of the correlation coefficient also show the same direction. This means that worker performance will increase along with the increase in the quality of human resources. Thus, this can show how effective and efficient Bawaslu employees are in carrying out their duties despite having heavy demands and a shortage of human resources.